Implementation of Islamic Religious Education (PAI) Learning in the Formation of Religious Character and Social Concern Attitudes - Miftahul Khoir; Kasuwi Saiban; Mustofa Mustofa (EDU-RELIGIA : Jurnal Keagamaan dan Pembelajarannya, 2023)
This study uses a qualitative approach with a descriptive analysis method. (1) in-depth interviews carried out with data collection techniques, (2) participatory observation, and (3) documentation. The data analysis process starts with data collection, editing (sorting), and checking the validity of the data. To check the validity of the data, the researchers used the data triangulation method. The results of this study indicate that: 1) The religious character of students at SMA Manggala Sakti Solokuro: The students have strong faith, devotion to Allah SWT, have strong faith, adhere to Islamic law, the students have a noble character, and have good character. As for Social Care: Devotion, help, kinship, caring, cooperation, and tolerance. 2) Implementation of PAI learning in the Formation of religious character and social care at SMA Manggala Sakti Solokuro, planning in the form of syllabus, socialization, lesson plans, implementation of Islamic Religious Education (PAI) learning in shaping religious character and social care at SMA Manggala Sakti Solokuro through 2 ways, namely intracurricular and extracurricular, evaluation with authentic assessment, assessment of reference criteria, reporting of learning outcomes. 3) Factors supporting the implementation of PAI learning in shaping religious character and social awareness include: prayer room, Islamic library, loudspeakers, culture of shaking hands with teachers before entering school, strong encouragement from the teacher council, availability of the Qur'an, teaching aids and LCD in the classroom. each class, there is an on-site evaluation. While the inhibiting factors include: student association outside school, different student backgrounds, environmental factors that are less supportive, the absence of a mosque, and friends' association